Geo Informatics Technology to Investigate the Expansion of the Chi River Basin’s Communities in Chaiyaphum Province - Tungchuvong, Lertrit; Payungvivattanakul , Chat; Tangchuwong, Vichuda (Interdisciplinary Academic and Research Journal, 2023)
Chaiyaphum Province is an area upstream of the Chi River in Nong Bua Daeng District and several tributaries. However, the pilot study also revealed several important land use and environmental issues. That is to say, there is still a lack of suitable land use plans and measures for watershed management in planning development to correspond with such phenomena, therefore, spatial information is needed to be used in decision-making, especially Geo-Informatics Technology for the benefit of land use. This research aimed to determine the expansion of the Chi River basin’s communities in Chaiyaphum province using satellite information in 2012 and 2022. Technically, obtained satellite data were identified by remote sensing, and the land utilization was calculated by overlay technique. Specifically, using the geoinformatics technology system evaluated the changes in water resources/marsh, communities, the forest, clear/ruined areas, and agricultural plantations, and analyzed the communities’ expansion at the Chi River basin in Chaiyaphum province. (1) As a result, in 2012, data was classified as water resource/marsh at 1,034,240 square meters (0.69 percent), communities at 4,028,020 square meters (2.69 percent), the forest at 100,073,240 square meters (66.68 percent), clear/ ruined areas at 20,815,606 square meters (13.87 percent), and agricultural plantations at 24,131,984 square meters (16.7 percent). (2) For the 2022 year, information was categorized as water resource/marsh at 1,621,500 square meters (1.09 percent), communities at 6,971,4000 square meters (4.64 percent), the forest at 79,003,620 square meters (52.64 percent), clear/ ruined areas at 40,423,880 square meters (26.93 percent), and agricultural plantations at 24,131,984 square meters (14.70 percent). (3) In essence, comparison results of the land utilization on the Chi River basin in Chaiyaphum province between 2012 and 2022 showed that water resource/marsh increased to 587,260 square meters (36.21 percent of total area), communities expanded to 2,943,380 square meters (42.22 percent of total area), the forest area declined to 21,069,620 square meters (21.05 percent of total area), clear/ ruined areas enlarged at 19,608,274 square meters (48.50 percent of total area), and agricultural plantations decreased at 2,069,294 square meters (8.57 percent of total area).